Allosteric Effects of the Anti-Psychotic Drug Trifluoperazine on the Energetics of Calcium Binding by Calmodulin - Feldkamp, Michael D. (2010)
Trifluoperazine (TFP; Stelazine™) is an antagonist of calmodulin (CaM), an essential regulator of calcium-dependent signal transduction. Reports differ regarding whether, or where, TFP binds to apo CaM. Three crystallographic structures (1CTR, 1A29, 1LIN) show TFP bound to (Ca(2+))(4)-CaM in ratios of 1, 2 or 4 TFP per CaM. In all of these, CaM domains adopt the “open” conformation seen in CaM-kinase complexes having increased calcium affinity. Most reports suggest TFP also increases calcium affinity of CaM. To compare TFP binding to apo CaM and (Ca(2+))(4)-CaM, and explore differential effects on the N- and C-domains of CaM, stoichiometric TFP titrations of CaM were monitored by (15)N-HSQC NMR. Two TFP bound to apo CaM, while four bound to (Ca(2+))(4)-CaM. In both cases, the preferred site was in the C-domain. During the titrations, biphasic responses for some resonances suggested inter-site interactions. TFP-binding sites in apo CaM appeared distinct from those in (Ca(2+))(4)-CaM. In equilibrium calcium titrations at defined ratios of TFP:CaM, TFP reduced calcium affinity at most levels tested; this is similar to the effect of many IQ-motifs on CaM. However, at the highest level tested, TFP raised the calcium affinity of the N-domain of CaM. A model of conformational switching is proposed to explain how TFP can exert opposing allosteric effects on calcium affinity by binding to different sites in the “closed”, “semi-open” and “open” domains of CaM. In physiological processes, apo CaM, as well as (Ca(2+))(4)-CaM, needs to be considered a potential target of drug action.